CHRISTIANITY AND ECOLOGY A CRITICAL STUDY ON THE CONTRIBUTION OF SDA THEOLOGY TOWARD ECOLOGY - M Rizal Abdi; Ferry Goodman Pardamean (Universitas Gadjah Mada, 2018)
To date, the controversial publication of Lynn White Jr’s article, The Historical Roots of Our Ecological Crisis (1967) ignites the fierce debate between theologian and academia in the field of religion and ecology about the guilt of Western Christianity toward modern ecological calamity. Meanwhile, as a Christian denomination that highly emphasizes on the second coming (the Advent) and the next life, Seventh-Day Adventist (SDA) Church doctrine is frequently accused as the reason why Christianity doctrine tend to put aside today’s environmental problem and more focused in the eternal next life. Though, at the same time, SDA Church also known for its emphasis on holistic life as well as one of the most advanced church in health and medical science. Given those handicap, the research tries to challenge those common perceptions about Christianity and ecology right into the heart of its criticism. By using literature-based research as methodology, this paper scrutinizes the doctrine of SDA church within the context of ecology as well as demonstrates how the SDA Church manifests its ecological doctrines. Furthermore, on wider discourse of religion and ecology, the explorations on SDA theology shows that rather than becoming a source of problem, the eschatological doctrine might become the driven-factor toward ecological practices nowadays.